2021
DOI: 10.1111/sjop.12691
|View full text |Cite
|
Sign up to set email alerts
|

The development of past and future life stories in adolescence: Overall emotional tone, coherence and life script events

Abstract: Research has shown that identity in adolescence takes the shape of a coherent life story that integrates the past with the present self and provides meaning and purpose in the person's life. One stable feature of narrative identity identified in adults is emotional tone. Here, the development of emotional tone in life stories was investigated across childhood and adolescence. A total of 142 adolescents aged 10 to 14 years wrote about their past weekend, their past and future life stories and generated a cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 46 publications
7
11
0
Order By: Relevance
“…We found that affective responses to SDFPs were very positive regardless of age, consistent with previous studies (D 'Argembeau et al, 2012;Raffard et al, 2020). These findings suggest that, through their future projections, individuals try to maintain a positive identity whatever their age, as well in adolescence (e.g., Ramsgaard & Bohn, 2021) as in ageing (e.g Sedikides & Gregg, 2008). Future projections allow a positive self to be enhanced (Grysman et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…We found that affective responses to SDFPs were very positive regardless of age, consistent with previous studies (D 'Argembeau et al, 2012;Raffard et al, 2020). These findings suggest that, through their future projections, individuals try to maintain a positive identity whatever their age, as well in adolescence (e.g., Ramsgaard & Bohn, 2021) as in ageing (e.g Sedikides & Gregg, 2008). Future projections allow a positive self to be enhanced (Grysman et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, we demonstrate that this bias is present when one imagines events with a counterpart self. This may indicate that the bias is independent from the associations with the self and that it may be related to generating positive events that are likely to be experienced in a culture, as had been previously proposed in the literature (Ramsgaard & Bohn, 2021).…”
Section: Discussionsupporting
confidence: 53%
“…Certainly, there is a large and growing body of evidence indicating that life scripts of the sort defined by Berntsen and Rubin ( 2004 ) can be found in every culture (Erdogan et al, 2008 ; Rubin et al, 2009 ; Zaragoza Scherman, 2013 ; Janssen et al, 2014 ; Zaragoza Scherman et al, 2017 ; Janssen and Haque, 2018 ). It also appears to be true that the life scripts are used in plotting out and assessing life trajectories, i.e., remembering one's past and predicting one's future (Hareven and Masoka, 1988 ; Greene, 1990 ; Greene et al, 1992 ; Schrauf and Rubin, 2001 ; Collins et al, 2007 ; Habermas, 2007 ; Berntsen and Jacobsen, 2008 ; Bohn and Berntsen, 2008 , 2011 , 2013 ; Thomsen and Berntsen, 2008 ; Berntsen and Bohn, 2010 ; Thomsen et al, 2011 ; Grysman et al, 2015 ; Enz et al, 2016 ; Ramsgaard and Bohn, 2021 ). There is also evidence that people experience distress when they fail to meet the milestones established by life scripts (Kuwabara et al, 2007 ; Rubin et al, 2009 ; Shanahan and Busseri, 2016 ; Dunlop et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%